PENGEMBANGAN PEMBERIAN CONTOH PENJUMLAHAN BILANGAN BULAT MENGGUNAKAN MULTI REPRESENTASI SEBAGAI MUATAN BAHAN AJAR - Deni Winda Sari; Mohamad Rif'at; Yundari Yundari (Jurnal AlphaEuclidEdu, 2022)
This study aims to describe: the feasibility level of teaching materials developed in the form of Student Worksheets, responses, and student learning outcomes after being given learning. The type of research used isResearch and Development (R&D)with the development model of Thiagarajan . The subjects in this study were the seventh grade students of the Asoka Singkawang Private Junior High School, which amounted to 20 people. The instruments used are questionnaires on the feasibility of teaching materials, student response questionnaires, and posttest questions. Data collection techniques: the feasibility of teaching materials was validated by experts, student responses were given a questionnaire, and learning outcomes were given posttest questions. Data were analyzed descriptively quantitatively. The results obtained: the feasibility level of teaching materials is 87.26% with very feasible criteria for use, student response questionnaires are 87% with very high criteria, meaning that student responses are very good, and student learning outcomes are classically fulfilled, namely 85% of students who achieve grades. minimal completeness. Conclusion: the developed teaching materials can be used in learning. Suggestion: further researchers can develop giving examples in learning mathematics and other learning using more diverse representations.